2005
DOI: 10.3409/1734916054663474
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of α-galactosides injected during embryogenesis on selected chicken traits

Abstract: Assessment of the effect of "-galactosides injected during embryogenesis on selected chicken traits. Folia biol. (Kraków) 53: 13-20. The effect of different doses of "-galactoside (RFOs) preparations from Pisum sativum L. cv. Opal, injected into eggs during embryogenesis, on maintaining a high number of bifidobacteria, selected chicken broiler traits and the lipoprotein level of blood were studied. Two independent experiments were conducted. In the first, Ringer water solution containing 1.763 mg/egg of fructo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 53 publications
5
30
0
Order By: Relevance
“…In Trial 1, both prebiotics injected in ovo (DN and BI) stimulated number of lactobacilli and bifidobacteria in chicken feces. This observation confirmed our earlier findings, that a single in ovo prebiotic (oligosaccharides) injection into 12-day-old chicken embryo leads to an increased number of bifidobacteria at the moment of hatching; it also ensures the long-term maintenance of a high level of intestinal bifidobacteria (Villaluenga et al, 2004;Pilarski et al, 2005). The mechanism of this process is of considerable interest, particularly in the light of the commonly held opinion that embryonic development of the chicken happens in a sterile environment (Amit-Romach et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In Trial 1, both prebiotics injected in ovo (DN and BI) stimulated number of lactobacilli and bifidobacteria in chicken feces. This observation confirmed our earlier findings, that a single in ovo prebiotic (oligosaccharides) injection into 12-day-old chicken embryo leads to an increased number of bifidobacteria at the moment of hatching; it also ensures the long-term maintenance of a high level of intestinal bifidobacteria (Villaluenga et al, 2004;Pilarski et al, 2005). The mechanism of this process is of considerable interest, particularly in the light of the commonly held opinion that embryonic development of the chicken happens in a sterile environment (Amit-Romach et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Based on chemical and physical features and dose of the injected substance, different site of injection (i.e. the embryo, the amnion, the allantois, the air cell or the yolk sac) and embryo age (0, 12, 17 or 18 days of incubation) have been used (Casas-Perez and Edens, 1995;Pilarski et al, 2005;Uni et al, 2005;Cheled-Shoval et al, 2011;Ebrahimnezhad et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spielmann et al (2008) observed that pea protein has a low methionine content and a high arginine content. The addition of pea meal as a source of protein into broiler diets can improve carcass quality and may result in favorable lipid profile, without adversely affecting growth performance traits (Igbasan & Guenter, 1996;Pilarski et al, 2005;Laudadio et al, 2012). The broiler serum proteins and fractions can be affected by the application of different feedstaff (Bingol et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, the opinion about harmfulness of RFOs has been recently negated. It is thought that these sugars belong to the class of favorable natural prebiotics (Gulewicz et al 2002;MartinezVillaluenga et al 2004;Pilarski et al 2005). On the basis of these results, discussion on influence of different N form on level of RFOs seems to be complicated.…”
Section: Influence Of Nitrogen Formsmentioning
confidence: 90%